Development of Ukrainian School and Educational Affair as a Basis of Professional Preparation of the Youth of Ukrainian Diaspora in the Second Half of the XX-th Century - Oksana Dzhus (Vasyl Stefanyk Precarpathian National University, 2019)
The formation and development of the Ukrainian school and educational affair as the basis for the professional training of Ukrainian youth in the Western countries in the second half of the XX-th century is examined in the article. The emphasis was given to the complexity and multiplicity of this process, which was caused by the socioeconomic and educational policies of the states, which became a new homeland for the Ukrainians, geography and compactness of their resettlement, employment in the different branches of the economy, the presence in the diaspora of the professional intelligentsia, its national awareness, the state religious life, etc. Accordingly, in different countries (Germany, Great Britain, Poland, Canada, USA, Australia, Argentina), this process was different, more or less intense and had results, but it still remains an object of interest as an important support of native cultural heritage, an inexhaustible source of preserving its spirituality bearers. The institutional forms and types of obtaining of pedagogical education by Ukrainians in the Western countries of the second half of the 20th century, the peculiarity of teaching and educational activities in different types of educational establishment and the main tendencies of the development of the Ukrainian school and educational affairs are presented. Among them: an expansion of the network of pre-school establishments, primary, secondary and high schools in connection with the arrival of emigrants to countries of Western Europe, America and Australia; public uniting efforts of leading Ukrainian public associations in preserving the national identity and spirituality of Ukrainians born outside Ukraine's native land; development of scientifically grounded, adapted to the needs and conditions of Ukrainians living in the diaspora of the theory of teaching and national education of younger generations; improving the content of studying and educational process in all types of schools, bringing it to the standards of the existing state education system and the increased requirements of economic and cultural life of the countries that have become a new homeland for Ukrainians.